2020
DOI: 10.4103/aam.aam_25_17
|View full text |Cite
|
Sign up to set email alerts
|

The millennial generation plastic surgery trainees in sub-Saharan Africa and social media: A review of the application of blogs, podcasts, and twitter as web-based learning tools

Abstract: The delivery of education and training in plastic surgery in Sub-Saharan Africa face increasing challenges. These include endemic shortages of plastic surgeons within postgraduate medical school faculties, the erosion of financial and clinical resources for teaching, and more recently, the millennial generation paradigm shift. It is generally accepted that the millennial generation will be more discerning and comfortable in their requirements for web-based learning content to support their education and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…While studying the differences between the millennials and the generations before them, it has become clear that their characteristics are uniform. 14 A study identified trends in using online reviews among plastic surgeons who performed gender confirming surgeries in the United States and assessed the influence of SM and other factors on online reviews that were obtained from 3 of the most popular physician-rating websites (HealthGrades.com [Denver, CO], Vitals.com [Lyndhurst, NJ], and WebMD.com [New York, NY]). Online ratings and comments were compared with age, years of practice, academic appointment, type of practice, geographic region of practice, SM use, and indexed articles.…”
mentioning
confidence: 99%
“…While studying the differences between the millennials and the generations before them, it has become clear that their characteristics are uniform. 14 A study identified trends in using online reviews among plastic surgeons who performed gender confirming surgeries in the United States and assessed the influence of SM and other factors on online reviews that were obtained from 3 of the most popular physician-rating websites (HealthGrades.com [Denver, CO], Vitals.com [Lyndhurst, NJ], and WebMD.com [New York, NY]). Online ratings and comments were compared with age, years of practice, academic appointment, type of practice, geographic region of practice, SM use, and indexed articles.…”
mentioning
confidence: 99%
“…Surgical blogs have experienced a recent renaissance [ 22 , 23 ]. Blogging is a good vehicle for topics not covered in traditional scientific literature and that require a more extensive coverage than the short format proposed on the other platforms.…”
Section: How Surgeons Use Social Media Platformsmentioning
confidence: 99%